Gender differences in the use of language learning strategies among ESL students / Reka Naidu Chandra Kumar - Reka Naidu , Chandra Kumar (2018)
This study aims to identify the types of strategies used by ESL learners and to determine the differences in strategy use between genders. A total of 172 (86 males, 86 females) students from the Malaysia University of Science and Technology (MUST) participated in the study. The data were gathered through Oxford’s (1990) strategy inventory for language learning (SILL) and twenty-four students who chose the higher scales in the questionnaire were selected for a semi-structured interview. The instrument, based on Oxford’s (1990) classification of language learning strategies are composed of 50 items in six subscales and 12 questions were extracted from SILL for the semi-structured interviews. The questionnaire data were analyzed through SPSS (19.0) to identify the types of language learning strategies used by the students while the interview data were analyzed qualitatively. The findings of the study revealed that the participants used metacognitive and social strategies more frequently compared to other learning strategies. The analysis of interview data showed that there were some similarities in terms of the six categories of language learning strategies used by the male and female students.